2002
DOI: 10.1089/107999002760624242
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monoclonal Antibodies Against GRIM-19, a Novel IFN-βand Retinoic Acid-Activated Regulator of Cell Death

Abstract: A combination of interferon-beta (IFN-beta) and all-trans retinoic acid (IFN/RA) induces tumor cell apoptosis via some unknown mechanisms. Apoptosis is a gene-directed process that limits the proliferation of undesired cells. Several genes are required to regulate cell death in the higher-order animals. Earlier, we employed a gene expression knockout technique to isolate cell death-related genes. A novel gene, the gene associated with retinoid-interferon-induced mortality-19 (GRIM-19), was found to be essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…It has been shown to interact exclusively with the transcriptional activating domain of Stat3 and inhibited transcriptional activation. 27,28,38 Recent studies have also shown that GRIM-19 expression is reduced or eliminated in a number of primary tumors. 29,35 Survivin is a downstream target of Stat3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown to interact exclusively with the transcriptional activating domain of Stat3 and inhibited transcriptional activation. 27,28,38 Recent studies have also shown that GRIM-19 expression is reduced or eliminated in a number of primary tumors. 29,35 Survivin is a downstream target of Stat3.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse monoclonal antibody against GRIM-19 was described earlier. 27 The criteria for grading immunohistochemical data for Survivin and GRIM-19 were similar to those described earlier. 28 Semiquantitative reverse transcription-PCR (RT-PCR) mRNA levels were determined using semiquantitative RT-PCR.…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, expression patterns of up-regulated G-protein-coupled receptors (G7) and down-regulated G-protein α-subunit (G16) indicate a complex regulation pattern of G proteins in nodules. The retinoid-interferon-induced mortality-19 gene (GRIM-19) and cytokine IK are novel cell death regulators characterized only in animals [43][44][45]. Further studies on their homologous genes in plants may provide new insights into apoptotic plant cell death.…”
Section: Discussionmentioning
confidence: 99%